1997
DOI: 10.1111/j.1365-2133.1997.tb01104.x
|View full text |Cite
|
Sign up to set email alerts
|

A controlled study of the effects of RU58841, a non-steroidal antiandrogen, on human hair production by balding scalp grafts maintained on testosterone-conditioned nude mice

Abstract: Human hair growth can be monitored for several months after the transplantation of scalp samples from men with androgen-dependent alopecia on to female nude mice. Hair production from balding sites has been shown to be inhibited in testosterone-conditioned nude mice. We used this recently reported model to study the effect of a new non-steroidal antiandrogen-RU58841-on human hair growth. Twenty productive scalp grafts from balding men were maintained for 8 months after grafting on to nude mice, and hair produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…7 It is, nevertheless, probable that in humans, topical flutamide induces systemic antiandrogenic effects since at least 16% is transcutaneously resorbed. 8 Preclinical data of another oral antiandrogen, an N-substituted aryl hydantoin, RU-58841 (Figure l), suggested topical safety since the cutaneous resorption was low, 9,10 however, one of the metabolites proved stable and strongly antiandrogenic, 11 and further development was abandoned. Another agent used in AGA is minoxidil, an antihypertensive drug which, by a mechanism yet to be clarified, increases hair thickness and anagen count.…”
mentioning
confidence: 99%
“…7 It is, nevertheless, probable that in humans, topical flutamide induces systemic antiandrogenic effects since at least 16% is transcutaneously resorbed. 8 Preclinical data of another oral antiandrogen, an N-substituted aryl hydantoin, RU-58841 (Figure l), suggested topical safety since the cutaneous resorption was low, 9,10 however, one of the metabolites proved stable and strongly antiandrogenic, 11 and further development was abandoned. Another agent used in AGA is minoxidil, an antihypertensive drug which, by a mechanism yet to be clarified, increases hair thickness and anagen count.…”
mentioning
confidence: 99%
“…4 Further work by De Brouweri et al conrmed the effect of RU58841 as an antiandrogen and baldness treatment by observing hair re-growth on bald human scalp segments that had been graed to mice. 8 As well as empirical studies, the biochemistry of RU58841 and other hydantoins have been evaluated for their effect as nonsteroidal testosterone inhibitors. 9 As the synthesis of RU58841 by Battmann et al (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A gel formulation of flutamide has been proposed to limit the systemic resorption [Sintov et al, 2000], but no clinical data have been reported. An experimental AA, N-substituted aryl hydantoin RU-58841, proved topically active in rodent and simian AGA models De Brouwer et al, 1997;Matias and Gaillard, 1995;Obana et al, 1997;Pan et al, 1998], but detection of a strongly antiandrogenic metabolite suggested that the compound was systemically resorbed, and further development has apparently been abandoned [Cousty-Berlin et al, 1994].…”
Section: Introductionmentioning
confidence: 99%